Pocket Book Design Based On Mathematical Puzzles To Improve The Mathematical Logical Intelligence Of Grade XI Students - Sirait, Abadihon Fazli; Lubis, Mara Samin (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
Teachers have a big role in developing and improving students' mathematical logical intelligence skills. However, teachers only focus on using package books in teaching in the classroom. As a result, students do not show a great attitude of enthusiasm, students struggle and are unable to think logically, creatively and innovatively in developing skills when doing math problems. Therefore, researchers are interested in creating a pocket book based on Mathematical Puzzles (TTM) class XI. This study aims to determine the feasibility, practicality and effectiveness of the pocketbook. This research is a research and development or R&D with a 4-D to 3-D model. The results of this study are the calculation value of V Aiken on the validation data of material experts of 0.903 and media experts of 0.8 are classified as feasible to use. Then the results of the calculation of V Aiken student response data of 0.932 and teacher response data of 0.894 are classified as very practical to use during learning. While the calculation of the t-Paired test in the pretest and posttest results obtained the value ,t-count.=6.1807, there is an increase in the mathematical logical intelligence of students so that the book is categorized as very effective. It can be concluded that the pocketbook based on class XI mathematical puzzles can improve the mathematical logical intelligence ability of class XI students.